Effect of Parity on Productive Performance and Calving Interval in Water Buffaloes - Nava-Trujillo, Héctor; Escalona-Muñoz, Juan; Carrillo-Fernández, Freygelinne; Parra-Olivero, Aldo (Journal of Buffalo Science, 2018)
The aim of this study was to determine the effect of the parity on productive performance (lactation length, total milk yield and milk yield by day of calving interval) and calving interval in water buffaloes. For this purpose, records of 663 lactations from 248 buffaloes were evaluated. Total milk yield was 1344.91 liters, lactation length was 291.20 days, calving interval was 453.55 days and milk by day of calving was 2.77 liters. Parity did not significantly affect total milk yield, but had a significant effect on lactation length, calving interval and milk by day of calving interval. First calving buffaloes had a longer lactation, a longer calving interval and in consequence lower productivity than buffaloes with two and three or more calving. Second calving buffaloes had intermediate and significantly different values than buffaloes with three or more calving. Calving interval was positively correlated with total milk yield (r = 0.34983, p <0.0001) and length of lactation (r = 0.67408, p = <0.0001); and negatively with milk by day of calving (r = -0.41263, p<0.0001). In conclusion, parity affected the productive performance and calving interval, with buffaloes of one and two calving being less productive due to a longer calving interval. An increase of milk yield is related with a longer calving interval, therefore, buffaloes of one and two calving, must be provided with optimal management conditions, which allow them to support milk yield and not to compromise the reproductive performance